2020
DOI: 10.1002/pca.2988
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian southeast brown propolis: gas chromatography method development for its volatile oil analysis, its antimicrobial and leishmanicidal activities evaluation

Abstract: Introduction Propolis is widely used in folk medicine, and many factors can affect its chemical composition, including abiotic factors that can influence plants and bees. Therefore, analytical methods are powerful techniques in the quality control of such products. Objective Develop and validate an analytical method for quantifying volatile compounds in Brazilian brown propolis, and evaluate its biological activities. Methods A gas chromatography flame ionisation detector (GC‐FID) analytical method was validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 25 publications
0
28
1
Order By: Relevance
“…The identification of α‐pinene and β‐pinene reinforces the hypothesis that Pinus , Eucalyptus and Araucaria angustifolia are the primary botanical sources of this propolis. The propolis used in this study proved to be different in its volatile composition from other brown propolis evaluated in the same region, [8] thus demonstrating the tremendous chemical diversity of this bee product.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…The identification of α‐pinene and β‐pinene reinforces the hypothesis that Pinus , Eucalyptus and Araucaria angustifolia are the primary botanical sources of this propolis. The propolis used in this study proved to be different in its volatile composition from other brown propolis evaluated in the same region, [8] thus demonstrating the tremendous chemical diversity of this bee product.…”
Section: Resultsmentioning
confidence: 73%
“…These compounds were not found in this brown propolis, revealing that B. dracunculifolia does not participate in its composition. In contrast to these findings, Ribeiro et al (2021) found markers of B. dracunculifolia in brown propolis from the southeastern region in Brazil [8] …”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Propolis with brown color is produced in several areas of the Brazilian territory. For example, brown propolis produced in the municipality of Cabo Verde (state of Minas Gerais, southeast Brazil) contains volatile oil with antimicrobial and leishmanicidal activities; the oil was shown to contain chiefly mono-and sesquiterpenes, in addition to γ-palmitolactone (Ribeiro et al 2020). However, the designation "brown propolis" refers mostly to products from the Brazilian south region (states of Paraná, Santa Catarina and Rio Grande do Sul), in areas with climate ranging from subtropical to temperate, dominated by Araucaria forests (Fig.…”
Section: Biomes Types and Compositionmentioning
confidence: 99%